THE TURKISH MODEL FOR IMPROVING IMO SURVEY RESULTS AND REDUCING SHIP ACCIDENTS - Acarer, Tayfun (My University, 2019)
The purpose of the IMO is to reduce the number of ship accidents, whichhave both economic and human costs. IMO regulations define what is requiredfor voyages to be safe. The primary mechanism for checking compliance aresurveys which are performed by member states. These checks are both technicaland human-related aspects of the ship. The former includes the features of theship and the equipment on board. The latter is regarding competencies of thepersonnel. There are significant discrepancies in the effectiveness of surveys indifferent regions. Over recent years Turkish ships have transitioned fromperforming poorly in surveys to performing well. We argue this is the result of aseries of legislative decisions. We identify which legislative decisions these areand present them as a repeatable recipe. Countries facing similar difficulties canfollow this example with the aim of improving IMO compliance; which in turnmeans economic benefits, fewer accidents and fewer lives lost.